Innovative Work Behavior and Islamic Work Ethic: The Role in Improving Employee Performance - Karina Fayada Putri; Faqih Nabhan (University of Darussalam Gontor, 2022)
The study begins with a research gap on the effect of organizational learning on employee performance based on the theory of planned behavior. This study analyzes the effect of organizational learning in encouraging innovative work behavior and Islamic work ethic to improve the performance of employees in the production department. The population is 1.155 employees of medium small and micro enterprise (MSME) furniture in Ggrobogan Regency. Using the purposive sampling method, this study used 100 respondents. We used multiple linear regression and path analysis using SPSS version 21 software to analyze the data. The result of the study is organizational learning can improve employee performance through innovative work behavior and Islamic work ethic.